Перспективи використання скидних вод для теплопостачання - Денисова, А. Є.; Троїцький, О. М. (НТУ "ХПІ", 2011)
The possibility of using different types of wastewater as a low-potential heat source for heat pump is analyzed. For heat pump cycles conversion coefficients for heat pumps cycle, working on waste waters, are calculated. The calculations have shown the perspectives of domestic and industrial wastewaters in the heat pump cycle.
Keywords: системи теплопостачання; природне паливо; енергоємність